Inheritance in Balinese Customary Law: Dynamics and Its Linkage With Hindu Law - I Gusti Ayu Jatiana Manik Wedanti; Ulio Ulio; I Made Sugita (Jurnal Indonesia Sosial Teknologi, 2024)
The inheritance system in Balinese customary inheritance law is known as the kapurusa system. This kapurusa system is patrilineal and is inspired by Hinduism. The issuance of the Decree of Pasamuhan Agung MUDP Bali Province in 2010 was an initial milestone in the change in the mindset of granting inheritance rights to girls and boys who married nyentana or married out with their wives. Therefore, it is necessary to research the dynamics of inheritance according to Balinese customary inheritance law and its relationship with Hindu law regarding inheritance. Using empirical-normative legal research methods, the findings in this research are the development of a shift in thinking that only sons have the right to inherit the gunakaya or wealth of their parents, which has begun to be seen from the existence of financial gifts or bequests which were previously not done by many people. Parents to their daughters or sons who are getting married is illegal, but now it is common practice. The connection between Hindu law and Balinese customary inheritance law in the field of inheritance can be seen from adopting the kapurusa or patrilineal system in Hindu law. However, it still allows daughters to be the principal heirs by being confirmed as sentana jeg or elevated to equal status with sons.